Spatial Utilization for the Skills Development Program in Yogyakarta Class IIB Correctional Facility for Women - Mutiara Anggi; Diananta Pramitasari (Jurnal Kawistara, 2021)
A correctional facility has been considered critical not only in accommodating prisoners but also facilitating vocational training that prepares the prisoners to reintegrate in society and thus would not recommit crimes. However, in reality the building of many correctional facilities are not prepared for this function. This is apparent in the correctional facility for women in Yogyakarta. The facility does not have its official building and is located in the men’s correctional facility. Those conditions impact the spatial limitations, including space to conduct the skills development program. This study aims to examine the spatial utilization for the skills development program in Yogyakarta prison for women by analyzing the relationship between the physical settings and the occurring activities there. By conducting place-centered mapping, questionnaire survey, and interview for data collection, this study showed that prisoners tend to seek to carry the vocational work in comfortable areas provided with better air condition that are not prepared for the training. This finding raises a concern about how a correctional facility should have adequate space that encourages social solidarity and provides enough spatial autonomy for the skills development program.